O início da imprensa e o webjornalismo: pontos de convergência - Minga, Ester Amaral de Paula (2013)
The object of study of this research is the journalistic praxis historically situated. The analysis covers from the emergence of the first leaflets in the fifteenth century, through its gradual evolution in newspapers with defined periodicity in the seventeenth century and the consolidation, during the nineteenth century, of the journalism as an autonomous field of discursive production, until the scenario occurred today in which news are produced and transmitted by non-professionals through platforms available on the internet. The goal is to identify points of convergence between the practice of production and circulation of news existing at the beginning of their trade, when there was not the professionalization of the journalism and the media system, and the current practice, by the internet. As specific objectives, it analyzes the similarities between the two periods and how this return to the origins has generated discussion within the journalistic field; it identifies the actions taken by the media system to participate in this process and tries to understand how this dynamics, similar to the past, has revitalized concepts like the public sphere. For its development, a literature analysis is carried out of authors such as John Thompson, responsible for the work of historical conceptualization of the media until its massified form, and Jurgen Habermas and his theory of the bourgeois public sphere; as well as case studies involving news produced and disseminated over the internet and its impact on the media system in society and among journalism professionals